Incidence of Venous Thromboembolism: A Community-based Study in Western France - Oger, Emmanuel; the EPI-GETBO Study Group (Thrombosis and Haemostasis, 2000)
The incidence of venous thromboembolism has been studied during one year in a defined population of 342,000 inhabitants. The overall incidence (95% confidence interval) of venous thromboembolism was found to be 1.83 per thousand per year (1.69 to 1.98). The incidences of deep venous thrombosis and pulmonary embolism were 1.24 per thousand per year (1.12 to 1.36) and 0.60 per thousand per year (0.52 to 0.69), respectively. The incidence of venous thromboembolism rose markedly with increasing age for both sexes; over the age of 75, the annual incidence reached 1 per 100. Sixty three percent of the patients were at home when venous thromboembolism occurred. Of these, sixteen percent had been previously hospitalised within three months. These results raise concerns on identification of medical patients at high risk and effective prophylaxis.
Keywords: Venous thromboembolism; epidemiology